Uterine Cancer Diagnosis and Treatment - Rajaram, Shalini; K, Chitrathara; Maheshwari, Amita; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2015)
Uterine cancers are the commonest malignancies of the female genital tract in the developed world, and are increasing in numbers world over because of obesity and other life-style changes. Many of these malignancies are hereditary and thus, a better understanding of the genetic and molecular biology is needed. This would lead to appropriate treatment plan for improving the quality of life and long-term survival. This book addresses, in depth, all aspects of uterine malignancies covering both carcinomas and sarcomas. The book is divided into seven sections; the first two sections deal with epidemiology, molecular aspects, familial cancers and pathology and the later sections focus on diagnosis, imaging techniques and comprehensive management of both early stage and advanced cancers. Surgical techniques, adjuvant chemotherapy and radiotherapy have been covered in detail. Apart from the open surgical methods, role of laparoscopy and emerging role of robotic surgery in the contemporary management of endometrial cancers have been discussed. Written by authors with expertise in the field of gynecologic oncology from premier institutes, this book provides up-to-date information on best practice management of uterine malignancies.
Section 1- Epidemiology, Molecular Biology, Familial Endometrial Cancer, Screening, Diagnosis and Staging -- Epidemiology of Endometrial Cancers and Uterine Sarcomas - Molecular Pathology and Cytogenetics of Endometrial Carcinoma, Carcinosarcoma and Uterine Sarcomas -- Hereditary cancers of the Endometrium – HNPCC syndrome and beyond -- Screening and Prevention of Carcinoma Endometrium -- Clinical Evaluation of Abnormal Uterine Bleeding -- Risk factors, Diagnosis and Staging of Endometrial Cancer -- Imaging in Uterine Malignancy -- Magnetic Resonance Imaging in Endometrial Cancer  Section II- Pathology of Uterine Cancers     Steroid Receptors in Normal Endometrium and in Endometrial Cancer -- Pathology of Endometrial Hyperplasia and Carcinoma -- Pathology of uterine sarcomas -- Prognostic and Predictive Factors in the Management of Carcinoma Endometrium.-     Section III- Surgical Anatomy& Early Stage Endometrial Cancer < Surgical Anatomy of the Uterus -- Endometrial Cancer Staging -- Sentinel Node Evaluation in Endometrial Cancer -- Surgery for Carcinoma Endometrium -- Ovarian preservation in carcinoma endometrium -- The Role of Lymphadenectomy in Endometrial Cancer -- Extra-peritoneal Laparoscopic Para-aortic Lymphadenectomy in Endometrial Cancer: Rationale & Surgical Technique -- Role of Laparoscopic and Robotic Surgery in Endometrial Cancer – The Inevitable Evolution -- Basics of Robotic Instrumentation & Robotic Assisted Surgery for Endometrial Cancer -- Adjuvant Radiation in Early Stage Endometrial Cancer -- Therapeutic options for early stage Uterine Papillary Serous Carcinomas, Carcinosarcomas, Clear cell and Mixed Cell Histologies -- Chemotherapy for high-risk early stage endometrial cancer: Current Evidence -- Diagnosis and Management of Stage II Endometrial Cancer -- Post treatment surveillance in endometrial cancer -- Section IV- Advanced Stage and Recurrent Endometrial Cancer< Surgery for advanced endometrial cancer -- Systemic treatment of advanced endometrial carcinoma -- Therapeutic Strategies in Recurrent and Metastatic Endometrial Cancer Section V- Uterine Sarcomas -- Uterine sarcomas: Risk Factors, Clinical Presentation, Diagnosis and Staging -- Surgical Management of Uterine Sarcoma -- Role of Radiation Therapy in Uterine Sarcoma  -- Role of Systemic therapy in the management of Uterine Sarcomas -- Surveillance of Uterine Sarcomas Section VI- Special case Scenarios    .-Metabolic Syndrome and Endometrial Cancer -- Management of Incompletely Staged Endometrial Cancer -- Synchronous cancers of ovary and endometrium -- Smooth Muscle Tumors of Uncertain Malignant Potential of Uterine origin -- Endometrial Cancers in young women:  Conservative management and fertility preserving options -- Hormone Therapy in normal postmenopausal women and after Endometrial Cancer -- Effects of Tamoxifen and Other SERMS in the Endometrium and   Follow up of Patients     Section VII- Palliative Care -- Palliative Care and End of Life Options for Patients with Endometrial Cancer  .
Keywords: Surgical oncology; Gynecology .; Abdominal surgery; Surgery; Surgical Oncology; Gynecology; Abdominal Surgery; General Surgery